2007
DOI: 10.1515/cclm.2007.259
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombogenic factors and reduced antioxidative defense in children and adolescents with pre-metabolic and metabolic syndrome

Abstract: Negative correlations between antioxidative defense parameters and BMI, abdominal obesity, insulin secretion, systolic blood pressure and atherogenic lipid factors, as well as correlations between PAI-1 and insulin resistance and basal glycemia in the metabolic syndrome group contribute to accelerated atherosclerosis. Positive correlations between PAI-1 and waist circumference and BMI, and negative correlations between BMI and antioxidative defense in the pre-metabolic syndrome patients show that this early st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 21 publications
5
15
0
1
Order By: Relevance
“…The pre-MetS status was defined as one or two [12] , and the MetS designation was made if three or more of the following five criteria were fulfilled: Central obesity (waist circumference > 90 cm based on Taiwanese criteria [13] ); Elevated blood pressure (defined as systolic blood pressure ≥ 130 mmHg or diastolic blood pressure ≥ 85 mmHg; Hyperglycemia, hypo-HDL cholesterolemia and hypertriglyceridemia (defined based on modified National Cholesterol Education Program Adult Treatment Panel Ⅲ criteria [14] as: fasting sugar ≥ 100 mg/dL, HDL < 40 mg/dL, and triglycerides ≥ 150 mg/dL). We specified e-ALT: e-ALT was defined as ALT > 40 U/mL, according to the standard reference limits used at Tao-Yuan General Hospital and other by studies [15] .…”
Section: Metsmentioning
confidence: 99%
“…The pre-MetS status was defined as one or two [12] , and the MetS designation was made if three or more of the following five criteria were fulfilled: Central obesity (waist circumference > 90 cm based on Taiwanese criteria [13] ); Elevated blood pressure (defined as systolic blood pressure ≥ 130 mmHg or diastolic blood pressure ≥ 85 mmHg; Hyperglycemia, hypo-HDL cholesterolemia and hypertriglyceridemia (defined based on modified National Cholesterol Education Program Adult Treatment Panel Ⅲ criteria [14] as: fasting sugar ≥ 100 mg/dL, HDL < 40 mg/dL, and triglycerides ≥ 150 mg/dL). We specified e-ALT: e-ALT was defined as ALT > 40 U/mL, according to the standard reference limits used at Tao-Yuan General Hospital and other by studies [15] .…”
Section: Metsmentioning
confidence: 99%
“…It is currently unclear if changes in circulating levels of these biomarkers as observed in children and adolescents (2)(3)(4)(5) could indicate the liability to increased CHD risk in adults, although, as has been reported in some populations, mainly Caucasian, it is likely that screening for these thrombogenic factors could be useful in the early prediction and prevention of CHD (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies on children, adolescents, and adult populations showed similar results. [12][13][14] Numerous studies indicate that insulin resistance is a central feature of metabolic syndrome; even the link between insulin resistance and most of the components of metabolic syndrome is not completely revealed. Insulin resistance is strongly associated with atherogenic dyslipidemia and proinflammatory parameters but less associated with hypertension and prothrombotic parameters.…”
Section: Discussionmentioning
confidence: 99%